2018
DOI: 10.1016/s1474-4422(17)30404-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of late seizures after ischaemic stroke with a novel prognostic model (the SeLECT score): a multivariable prediction model development and validation study

Abstract: Background: Stroke is one of the leading causes of acquired epilepsy in adults. An

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
237
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(277 citation statements)
references
References 40 publications
(16 reference statements)
16
237
1
4
Order By: Relevance
“…Stroke‐related epilepsy prediction tools can help to risk‐stratify stroke survivors who are most likely to benefit from AED therapy. These could also become an important basic model in research that aims to prevent the transformation of infarcted tissue into an epileptic focus . Although many studies have identified variables associated with STRE, a well‐validated instrument that synthesizes clinical characteristics individually and objectively is lacking.…”
Section: Epidemiologymentioning
confidence: 99%
“…Stroke‐related epilepsy prediction tools can help to risk‐stratify stroke survivors who are most likely to benefit from AED therapy. These could also become an important basic model in research that aims to prevent the transformation of infarcted tissue into an epileptic focus . Although many studies have identified variables associated with STRE, a well‐validated instrument that synthesizes clinical characteristics individually and objectively is lacking.…”
Section: Epidemiologymentioning
confidence: 99%
“…Monitoring tools have been presented in the clinical literature, but have limited appearances in the statistical literature. A recent clinical study, which was aimed at predicting late seizures after ischemic stroke using Cox proportional hazard modeling, presented a downloadable smart phone app for making predictions with new patients . A joint longitudinal‐survival model for prostate cancer recurrence was accompanied by an online risk calculator, providing predictions of up to 3 years in advance .…”
Section: Introductionmentioning
confidence: 99%
“…However, our choice of flow cytometry markers reflects all major leukocyte lineages. Additionally,multiple papers have developed scores and multi-dimensional models based on pre-selected markers (Galovic et al, 2018;Liu et al, 2017;Schrag et al, 2017). Nonetheless, we cannot exclude that there are further useful markers to distinguish MS and NS, that we did not investigate and did not include in our model.…”
Section: Discussionmentioning
confidence: 97%